Effect of culture conditions on the physicochemical properties and antioxidant activities of polysaccharides from Nostoc flagelliforme. (15th October 2018) - Shen, Shi-gang; Jia, Shi-ru; Wu, Yi-kai; Yan, Rong-rong; Lin, Ya-Hui; Zhao, Dong-xue; Han, Pei-pei
Highlights: Three polysaccharides were obtained under different culture conditions. Glu-CPS-1 exhibited the highest antioxidant activity in vitro. Proper culture conditions can enhance the antioxidant activity of polysaccharides. Abstract: Three polysaccharides (WL-CPS-1, NaCl-CPS-1 and Glu-CPS-1) were extracted and purified from Nostoc flagelliforme under normal, salt stress and mixotrophic culture conditions respectively. Their physicochemical properties and antioxidant activities were investigated. WL-CPS-1, NaCl-CPS-1 and Glu-CPS-1 chemical composition differed in sugar and uronic acid contents, and they were composed of nine constituent monosaccharides and one uronic acid with different ratios, with the average molecular weights of 1.02 × 10 3, 1.12 × 10 3 and 1.33 × 10 3 kDa, respectively. They presented similar fourier transform infrared spectra, but different surface morphology, chain length and branching. Antioxidant assay showed that they all exhibited strong scavenging activity on ABTS + and hydroxyl radicals and moderate activity on DPPH radical. Glu-CPS-1 exhibited the highest antioxidant activity suggested culture conditions could regulate the bioactivity through influencing the structure and properties. These findings demonstrated the potential application of proper regulation of culture conditions in the development of polysaccharides with high antioxidant activity.